2013
DOI: 10.1111/jocn.12438
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mandatory preclinical education on exposure to injuries as reported by Italian nursing students: a 15‐year case–control, multicentre study

Abstract: What does this paper contribute to the wider global clinical community?• A significantly increased occurrence of injury exposure is reported by those students attending a mandatory preclinical education intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In a previous study, a total of 239 cases of injury exposures were reported by 2514 NSs (3.15 incidence/100,000 clinical training days). Among the injury exposures, 187 NSs reported being contaminated by body fluids (92.5% by blood and 7.5% by urine, saliva and others) [2]. Because of this, nursing students, like any other healthcare worker (HCW), are at a high risk of acquiring infections if proper protection has not been instituted.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, a total of 239 cases of injury exposures were reported by 2514 NSs (3.15 incidence/100,000 clinical training days). Among the injury exposures, 187 NSs reported being contaminated by body fluids (92.5% by blood and 7.5% by urine, saliva and others) [2]. Because of this, nursing students, like any other healthcare worker (HCW), are at a high risk of acquiring infections if proper protection has not been instituted.…”
Section: Introductionmentioning
confidence: 99%